2001
DOI: 10.1083/jcb.153.3.555
|View full text |Cite
|
Sign up to set email alerts
|

Δn89β-Catenin Induces Precocious Development, Differentiation, and Neoplasia in Mammary Gland

Abstract: To investigate the role of β-catenin in mammary gland development and neoplasia, we expressed a stabilized, transcriptionally active form of β-catenin lacking the NH2-terminal 89 amino acids (ΔN89β-catenin) under the control of the mouse mammary tumor virus long terminal repeat. Our results show that ΔN89β-catenin induces precocious lobuloalveolar development and differentiation in the mammary glands of both male and female mice. Virgin ΔN89β-catenin mammary glands resemble those found in wild-type (wt) pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
210
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(224 citation statements)
references
References 67 publications
11
210
3
Order By: Relevance
“…TG expression of a stabilized mutant of b-catenin induces mammary tumors that bear similarities to tumors in Wnt-1 TG mice (Imbert et al, 2001;Michaelson and Leder, 2001). To our surprise, however, neither ER nor PR was detected in five tumors from b-catenin TG mice ( Figure 1a; see Discussion for possible explanations).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TG expression of a stabilized mutant of b-catenin induces mammary tumors that bear similarities to tumors in Wnt-1 TG mice (Imbert et al, 2001;Michaelson and Leder, 2001). To our surprise, however, neither ER nor PR was detected in five tumors from b-catenin TG mice ( Figure 1a; see Discussion for possible explanations).…”
Section: Resultsmentioning
confidence: 99%
“…TG mice expressing Wnt-1 (Tsukamoto et al, 1988), the Neu protooncogene (Guy et al, 1992), an N-terminus-deleted, stabilized mutant of b-catenin (Imbert et al, 2001) and c-Myc (Stewart et al, 1984) have been described, as have mice harboring targeted inactivating mutations of Pten (Podsypanina et al, 1999) and p53 (Jacks et al, 1994). All TG mice were maintained on the FVB background, but Pten and p53 mutant mice were on mixed backgrounds of 129, FVB and C57/BL6.…”
Section: Micementioning
confidence: 99%
“…E-cadherin is required for normal differentiation and survival of the epithelium. b-catenin/LEF signaling in the epithelium appears to be important to the formation of mammary buds, ductal extension, and alveologenesis, as well as maintenance of the normal adult mammary gland [Imbert et al, 2001;Hatsell et al, 2003]. Transmembrane P-cadherin expressed by the myoepithelium may play a role in regulating epithelial cell proliferation and invasion, whereas the role of sP-cadherin in the lactating gland or the suckling young is not understood.…”
Section: Cadherins and Catenins In The Normal Mammary Glandmentioning
confidence: 99%
“…Furthermore, in lymph node negative breast tumors, the presence of high levels of b-catenin protein in combination with high levels of P53 protein correlated with poor survival of patients (Chung et al, 2004), indicating that b-catenin and P53 may have a combinatorial effect on tumor progression. In addition to the human data, studies using mouse models have demonstrated a role for b-catenin in initiating mammary tumors (Imbert et al, 2001;Michaelson and Leder, 2001).…”
mentioning
confidence: 99%